20 years later: deliberate practice and the development of expertise in sport - Baker, J.; Young, B. (International Review of Sport and Exercise Psychology, 2014)
Twenty-one years ago, Ericsson, Krampe and Tesch-Romer published their seminal work expounding the notion of deliberate practice in explaining the development of expertise. This concept has since become extremely influential in the fields of sport psychology and motor learning. This review evaluates current understanding of deliberate practice in sport skill acquisition with an emphasis on the role of deliberate practice in distinguishing expert athletes from non-experts. In particular, we re-examine the original tenets of Ericsson et al.'s framework to (a) evaluate the sport-related research supporting their claims and (b) identify remaining research questions in this area. The review highlights the overall importance of deliberate practice in the development of expert sport performers; however, our understanding is far from complete. Several directions for future research are highlighted, including the need for more rigorous research designs and statistical models that can evaluate changes in developmental and contextual factors across development. Finally, we advocate for a more thorough understanding of the implications of a `deliberate practice approach` for coaching science.